Program Perbaikan Data Absensi Fingerprint di Perusahaan Alfa Premium New Star - Oentoro, Benaya; Maxmiliano, Petrus; Alexander, Edwin (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
Nowadays, every company has implemented sophisticated technology and keeps up with the times, such as manual attendance being switched to fingerprint, which no one can manipulate. The fingerprint attendance system is used to manage employee absences in various companies. The company Alfa Premium New Star currently uses 2 attendance systems, the manual system being the time clock and the fingerprint machine. The fingerprint system makes it easier for company admins to carry out overall employee attendance. However, the current implementation of the machine is not without its shortcomings. The program we developed uses an algorithm to handle problems by analyzing existing attendance data.